The Implementation of Land Rights Certification Linked to Implementation of Law Number 28 Year 2009 concerning Regional Taxes and Levies in Medan - Abdurrahman Harits Ketaren (Budapest International Research and Critics University, 2021)
Requests for land registration for the first time, t are subject to PPh F PHTB and BPHTB. Specifically in the Systematic and Complete Land Registration program (PTSL) calculation of BPHTB in is important, because it becomes the basis for other provisions such as the end of the BPHTB payment period, sanctions, etc. Notary as PPAT, as the maker of the deed also plays a role when dealing with the PTSL applicant who bases his application with the deed transfer of land rights. The results of this study indicate that the Mayor can grant BPHTB reduction requests submitted by PTSL applicants based on propriety, fairness and fairness. PTSL applicants who are not or have not been able to pay BPHTB for the land concerned can still be issued a Land Rights Certificate which must make the statement of BPHTB owed. Constraints related to the collection of BPHTB in the PTSL program, the society did not get socialization about BPHTB from the Tax Officer, the information was actually conveyed by the Land Officer. This made many residents disappointed because the initial counseling was conveyed that the PTSL program was free, but in fact there was a payment so that many applicants did not participate the PTSL program.